Long-carbon-chain quaternary ammonium salt modified dough type electrolyte as well as preparation method and application thereof
By introducing long carbon chain quaternary ammonium salts and sodium alginate into the electrolytes of zinc air batteries, a cross-linked network structure is formed, which solves the problems of easy leakage and low conductivity of existing electrolytes, and significantly improves the performance and life of zinc air batteries.
Patent Information
- Application Number
- CN202411704264.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
AI Technical Summary
The electrolytes of existing zinc-air batteries have problems such as high volatility, easy leakage, low ionic conductivity and poor structural stability during use, which affects the safety and life of the battery.
The dough-type electrolyte modified with long carbon chain quaternary ammonium salt is used to form a cross-linking network structure by introducing sodium alginate and polymer into the electrolyte frame, enhancing mechanical strength and structural stability, and improving conductivity through salt-based modifiers.
The high mechanical strength, structural stability and high conductivity of the electrolyte are achieved, which significantly improves the energy storage performance, flexibility and safety of zinc air batteries and extends the service life of the battery.
Smart Images

Figure CN119725898A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energy storage devices, and particularly relates to a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt, and a preparation method and application thereof. Background Art
[0002] Zinc-air batteries have attracted much attention due to their high energy density, low cost and environmentally friendly characteristics, and are a hot research direction for the next generation of energy storage devices. Compared with lithium-ion batteries, zinc-air batteries have obvious advantages in theoretical energy density because they use oxygen in the air as an active substance, which can theoretically greatly reduce the weight of the battery. In addition, zinc is abundant, inexpensive, non-toxic and safe, making it have wide application potential in electric vehicles, renewable energy storage and portable electronic devices. However, the performance and life of zinc-air batteries depend largely on the properties of the electrolyte. The electrolyte not only needs to have high ionic conductivity to improve battery efficiency, but also needs to maintain chemical and mechanical stability during use. Therefore, developing an excellent electrolyte material is the key to improving the performance of zinc-air batteries.
[0003] In recent years, the research focus of zinc-air batteries has been on the development of liquid electrolytes and gel electrolytes. Liquid electrolytes (such as aqueous KOH solutions) have high ionic conductivity, but have disadvantages such as high volatility and easy leakage, which limit battery safety and cycle life. In addition, liquid electrolytes easily react with CO2 in the air to form carbonate deposits, further reducing battery performance. In order to solve the problems of liquid electrolytes, gel electrolytes have gradually attracted attention. Gel electrolytes improve mechanical strength and reduce liquid flow by introducing polymer networks into the liquid. Although gel electrolytes solve the problems of leakage and evaporation to a certain extent, their ionic conductivity is generally low, and the gel structure may degrade after long-term use, affecting the stability and life of the battery. Therefore, existing electrolytes still face many challenges in improving the performance of zinc-air batteries. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt and a preparation method and application thereof.
[0005] The invention provides an electrolyte, wherein the electrolyte components include an electrolyte framework, a salt modifier and an electrolyte matrix; wherein the electrolyte framework is formed into a cross-linked network framework with components containing sodium alginate SA, a polymer and a long carbon chain quaternary ammonium salt.
[0006] The electrolytes are all in a dough-like form and have good ductility.
[0007] Furthermore, the long carbon chain quaternary ammonium salt accounts for 1%-15% of the total electrolyte mass; the salt modifier accounts for 0.1%-5% of the total electrolyte mass.
[0008] The salt modifier and electrolyte matrix are arranged in the electrolyte framework;
[0009] Preferably, the long carbon chain quaternary ammonium salt is a quaternary ammonium salt having an alkyl carbon chain number of 9 or more, and more preferably, the long carbon chain quaternary ammonium salt is a quaternary ammonium salt having an alkyl carbon chain number of 12-18.
[0010] Furthermore, the long carbon chain quaternary ammonium salt includes one or more of dodecyltrimethylammonium chloride DTAC, hexadecyltrimethylammonium chloride CTAC, octadecyltrimethylammonium chloride STAC, and the like.
[0011] Preferably, the polymer includes one or more of cyclodextrin, polyacrylic acid PAA, polyethylene glycol PEG, polyvinyl alcohol PVA, sodium polyacrylate PAANa, polyacrylamide PAM, polyvinylidene fluoride PVDF copolymer, and polyethylene oxide PEO.
[0012] Further preferably, the polymer is two or more of cyclodextrin, polyacrylic acid PAA, polyethylene glycol PEG, polyvinyl alcohol PVA, sodium polyacrylate PAANa, polyacrylamide PAM, polyvinylidene fluoride PVDF copolymer, and polyethylene oxide PEO.
[0013] Preferably, the salt modifier includes one or more of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, potassium iodide, potassium bromide, 2-acrylamido-2-methylpropanesulfonic acid sodium salt, sodium dodecylbenzenesulfonate, and 1-ethyl-3-methylimidazole acetate EMIMAc.
[0014] Preferably, the electrolyte matrix includes an alkaline electrolyte matrix or a neutral electrolyte matrix; wherein the alkaline electrolyte matrix includes potassium hydroxide, and further, the concentration of potassium hydroxide is 2 to 12M; the neutral electrolyte matrix includes salts formed by zinc trifluoromethanesulfonate and lithium bistrifluoromethanesulfonyl imide at different concentrations, and further, the molar ratio of zinc trifluoromethanesulfonate to lithium bistrifluoromethanesulfonyl imide is (0.1-1):4.
[0015] The present invention provides a method for preparing an electrolyte, comprising:
[0016] (1) mixing a long carbon chain quaternary ammonium salt and a polymer solution, and then mixing with an initiator and a cross-linking agent, and degassing to obtain a mixed solution; (2) mixing the mixed solution, an electrolyte matrix, and a salt modifier, cross-linking reaction, and then adding sodium alginate SA to mix to obtain a dough-type electrolyte.
[0017] Preferably, in step (1), the mass ratio of the long carbon chain quaternary ammonium salt, the initiator, and the crosslinking agent is (30-100):(1-6):(1-2);
[0018] Preferably, the polymer solution in step (1) is a polymer aqueous solution.
[0019] The mass percentage concentration of the polymer solution in step (1) is 0.5-50%.
[0020] For example, polyacrylic acid (PAA) uses a PAA aqueous solution with a mass concentration of 0.5%-30%, polyethylene glycol (PEG) uses a PEG aqueous solution with a mass concentration of 2%-50%, and polyvinyl alcohol (PVA) uses a PVA aqueous solution with a mass concentration of 5%-40%. The mass percentage concentration of the polymer solution is selected according to actual conditions.
[0021] Preferably, in the step (1), the initiator is one of potassium persulfate, ammonium persulfate and azobisisobutyronitrile; and the cross-linking agent is one of N,N'-methylenebisacrylamide, glutaraldehyde and diglycidyl ether.
[0022] In the step (1), the long carbon chain quaternary ammonium salt is ground long carbon chain quaternary ammonium salt.
[0023] In the step (1), the long carbon chain quaternary ammonium salt is added to the polymer solution and mixed.
[0024] In step (1), an initiator and a cross-linking agent are added under stirring.
[0025] Preferably, the degassing in step (1) is performed by vacuuming at room temperature to remove bubbles, wherein the vacuuming is performed 3-5 times.
[0026] The long carbon chain quaternary ammonium salt accounts for 1%-15% of the total electrolyte mass; the salt modifier accounts for 1%-15% of the total electrolyte mass.
[0027] In the step (2), the mixed solution, the electrolyte matrix and the salt modifier are mixed: the electrolyte matrix is added to the mixed solution, stirred evenly, and the salt modifier is added.
[0028] Preferably, in step (2), the mass ratio of the electrolyte matrix to the polymer solution is (0.5-30):(1-5).
[0029] Furthermore, the mass ratio of the alkaline electrolyte matrix to the polymer solution is (0.1-5):4; the mass ratio of the neutral electrolyte matrix to the polymer solution is (1-20):1.
[0030] In step (2), the electrolyte matrix and the salt modifier are added to the mixed solution under ice bath conditions.
[0031] The mixing in step (2) is stirring for 10-20 minutes.
[0032] Preferably, the cross-linking reaction in step (2) is carried out at 40-80° C. for 15-40 min, and the cross-linking reaction is carried out under static conditions.
[0033] Preferably, in step (2), sodium alginate is added and stirred until the granular feeling disappears.
[0034] The invention provides a zinc-air battery, which comprises a positive electrode, a negative electrode and the electrolyte.
[0035] The present invention provides applications of the electrolyte and the zinc-air battery in energy storage, flexible electronics and green energy systems.
[0036] 1. The cross-linked network formed between quaternary ammonium salt, SA and polymer enhances the mechanical strength and structural stability of the electrolyte
[0037] Quaternary ammonium salt NR 4+ Ions and carboxylic acid groups on SA can form electrostatic effects through ion exchange. This combination enhances the ion migration rate of the electrolyte and improves its overall conductivity. Under the action of the polymer, the quaternary ammonium salt can form a cross-linked network with these polymers through hydrogen bonds and other chemical bonds. This cross-linked network provides the electrolyte with good mechanical strength and structural stability, reduces degradation and loss during the cycle, and ensures the long-term stable operation of the battery.
[0038] 2. Compared with short-chain quaternary ammonium salts, electrolytes modified with long-chain quaternary ammonium salts exhibit higher stability in alkaline environments.
[0039] Short-chain quaternary ammonium salts have good miscibility with water and alkaline media due to their shorter carbon chains, which makes them easier to diffuse in solutions and therefore more vulnerable to attack by alkaline components. Long carbon chains can provide significant hydrophobicity, forming a physical barrier that reduces the direct contact between the cationic core and the hydroxyl groups in the alkaline medium. This barrier effect reduces the risk of deammoniation reactions of quaternary ammonium salts in alkaline environments (i.e., the breaking of CN bonds). The steric hindrance effect brought by the long carbon chain makes the quaternary ammonium cation less susceptible to external attacks, and the long carbon chain quaternary ammonium salts can self-assemble into micellar structures in the solution, further protecting the cationic core. This self-assembly behavior effectively improves the stability and conductivity of the electrolyte under alkaline conditions, and then through the synergistic effect of the cross-linked network and the long carbon chain, the ion migration rate of the electrolyte is increased, thereby improving the output performance of the zinc-air battery.
[0040] 3. Dough-type electrolyte has good ductility and high safety.
[0041] SA can form a quasi-solid state with high viscosity under strong alkaline conditions, making the electrolyte dough-like with high plasticity and good viscoelasticity. It can effectively solve the problem of easy leakage and volatilization of liquid electrolytes, while also maintaining the excellent mechanical properties of gel electrolytes to meet the needs of different application environments. In neutral electrolytes (such as ZnSO4, Zn(CF3SO3)2), SA helps to improve the mobility of zinc ions and the overall conductivity of the electrolyte by forming an ion conductive network. When used as a skeleton material for neutral electrolytes, it can improve the flexibility and stability of the entire device. Due to SA's excellent ionic conductivity, dendrite suppression ability, high mechanical stability and environmental protection, the sandwich-structured zinc-air battery assembled with the synthesized electrolyte has electrochemical properties such as long cycle life, high discharge power density and high specific capacity, while also having good flexibility, which improves the safety performance of zinc-air batteries.
[0042] 4. The addition of salt modifiers enhances the conductivity of the electrolyte.
[0043] Metal salts and organic salts are added to the electrolyte as modifiers (such as zinc sulfate, zinc acetate, potassium iodide, EMIMAc, etc.). These modifiers inhibit the self-corrosion of zinc through interaction with zinc ions, reduce the self-discharge rate of the battery, and enhance the conductivity and chemical stability of the electrolyte.
[0044] 5. The preparation method of the electrolyte is relatively simple and easy to achieve large-scale preparation.
[0045] The preparation method includes precisely controlled cross-linking and modification steps to ensure the uniformity and stability of the electrolyte. The structural integrity and electrochemical performance of the electrolyte are improved through optimized process parameters (such as temperature, time, component ratio, etc.).
[0046] In the present invention, a long carbon chain quaternary ammonium salt, which is more stable than a short chain, is introduced into an electrolyte framework composed of sodium alginate (SA) and a polymer (such as polyacrylic acid (PAA), polyethylene glycol (PEG), polyvinyl alcohol (PVA), sodium polyacrylate (PAANa), polyacrylamide (PAM), etc.) to form a cross-link to enhance the ionic conductivity, mechanical strength and stability of the electrolyte, thereby improving the overall performance and service life of the zinc-air battery. The preparation steps of the dough-type electrolyte include the processes of raw material selection, mixing, reaction curing and molding, and the preparation method is relatively simple and easy to achieve large-scale preparation.
[0047] Beneficial Effects
[0048] The present invention innovatively combines polymers, long carbon chain quaternary ammonium salts and sodium alginate to form a more stable cross-linked network structure, and introduces a modifier to improve the stability and conductivity of the electrolyte, thereby overcoming the defects of the prior art and providing an electrolyte for zinc-air batteries with high water absorption and retention, high stability and good ductility.
[0049] The electrolyte obtained by the present invention is applied to zinc-air batteries and has battery properties such as high conductivity, high discharge power, and excellent cycle stability, which greatly improves the safety performance and service life of flexible zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 A digital photo of the electrolyte prepared in Example 1;
[0051] Figure 2 The impedance spectra and ionic conductivity comparison diagrams of the electrolytes prepared in Example 1 and the comparative example;
[0052] Figure 3 The open circuit voltage comparison diagram of the zinc-air battery prepared in Example 1 and the comparative example;
[0053] Figure 4 The zinc-air battery prepared in Example 1 and the comparative example was 2 Comparison chart of discharge performance under current density and rate discharge performance;
[0054] Figure 5 The zinc-air battery prepared in Example 1 and the comparative example was 2 Comparison of charge and discharge cycle performance under current density;
[0055] Figure 6 The voltage stability test diagram of the zinc-air battery assembled with the electrolyte prepared in Example 1 after bending, the macroscopic diagram after bending at different angles, and the demonstration diagram of powering the device. DETAILED DESCRIPTION
[0056] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application. The relevant tests in the embodiments relate to the supplementary test conditions.
[0057] Example 1
[0058] A method for preparing a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt for a zinc-air battery comprises the following steps:
[0059] 3 g of 1 wt.% PAA aqueous solution was mixed with 1 g of 10 wt.% PVA aqueous solution. 0.5 g of dodecyltrimethylammonium chloride (DTAC) was weighed and ground into a mortar, and then added into the mixed solution together with 13 mg of potassium persulfate and 6.5 mg of N,N'-methylenebisacrylamide, and stirred thoroughly. The mixture was evacuated three times at room temperature. The resulting solution was placed in an ice bath, and 0.05 g of zinc acetate and 2 g of KOH were slowly added thereto. After stirring for 20 min, the mixture was placed in a 60°C oven and allowed to stand for 20 min. After being taken out and cooled to room temperature, 0.7 g of SA was added, and the mixture was immediately mixed and kneaded until the granularity disappeared to obtain a dough-type electrolyte named LQAS / SA / PVAA.
[0060] The negative electrode zinc foil, the electrolyte prepared above and the positive electrode were assembled into a zinc-air battery in a sandwich structure. The open circuit voltage of the battery was 1.55 V, the energy density was 210 Wh / kg, and the 2 At a current density of 1.5 %, the battery can be charged and discharged for 15 minutes and can be cycled stably for 95 hours.
[0061] Example 2
[0062] A method for preparing a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt for a zinc-air battery comprises the following steps: mixing 1 g of a 5 wt.% PEG aqueous solution with 3 g of a 1 wt.% PAA aqueous solution, weighing 0.4 g of dodecyltrimethylammonium chloride (DTAC), replacing the 3 g of a 1 wt.% PAA aqueous solution mixed with 1 g of a 10 wt.% PVA aqueous solution in Example 1, and weighing 0.5 g of dodecyltrimethylammonium chloride (DTAC). The other steps and conditions are the same as those in Example 1. The negative electrode zinc foil, the electrolyte prepared above, and the positive electrode are assembled into a zinc-air battery in a sandwich structure. The battery has an open circuit voltage of 1.43 V, an energy density of 187 Wh / kg, and an energy density of 1.5 mA / cm 2 At a current density of 15 minutes, the battery can be cycled for 75 hours.
[0063] Example 3
[0064] A method for preparing a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt for a zinc-air battery is as described in Example 1, except that 0.3 g of hexadecyltrimethylammonium chloride (CTAC) is weighed to replace dodecyltrimethylammonium chloride (DTAC) in Example 1, and the other steps and conditions are the same as those in Example 1. The negative electrode zinc foil, the electrolyte prepared above, and the positive electrode are assembled into a zinc-air battery in a sandwich structure. The battery has an open circuit voltage of 1.50 V, an energy density of 203 Wh / kg, and an energy density of 1.50 V at 5 mA / cm 2 At a current density of 15 minutes, the battery can be cycled for 95 hours.
[0065] Example 4
[0066] A method for preparing a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt for a zinc-air battery is as described in Example 1, except that 0.2 g of octadecyltrimethylammonium chloride (STAC) is weighed to replace dodecyltrimethylammonium chloride (DTAC) in Example 1, and the other steps and conditions are the same as those in Example 1. The negative electrode zinc foil, the electrolyte prepared above, and the positive electrode are assembled into a zinc-air battery in a sandwich structure. The battery has an open circuit voltage of 1.41 V, an energy density of 213 Wh / kg, and an energy density of 1.5 W / kg at 5 mA / cm 2 At a current density of 15 minutes, the battery can be cycled for 100 hours.
[0067] Example 5
[0068] A method for preparing a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt for a zinc-air battery comprises the following steps:
[0069] Take 0.7g 1wt.% PAA aqueous solution and 0.15g 10wt.% PVA aqueous solution and mix them. Weigh 0.2g dodecyltrimethylammonium chloride (DTAC) and grind it in a mortar. Then add it to the above mixed solution together with 13mg potassium persulfate and 6.5mg N,N'-methylenebisacrylamide and stir it thoroughly. The stirring temperature is set to 15°C, the speed n=50rpm, and v=2m / s. Vacuum it 3 times at room temperature. Put the obtained solution into an ice bath, slowly add 0.05g sodium dodecylbenzene sulfonate and 6g high-concentration salt solution with a molar ratio of LiTFSI:Zn(OTF)2=20:1, stir for 20min, put it into a 60°C oven and let it stand for 20min. Take it out and cool it to room temperature. Then add 1g SA and mix and knead it immediately until the granularity disappears to obtain a dough-type electrolyte. The negative electrode zinc foil, the electrolyte prepared above and the positive electrode were assembled into a zinc-air battery in a sandwich structure. The open circuit voltage of the battery was 1.05 V, the energy density was 103 Wh / kg, and the 2 At a current density of 15 minutes, the battery can be cycled for 120 hours.
[0070] Comparative Example 1
[0071] A method for preparing a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt for a zinc-air battery is as described in Example 1, except that no quaternary ammonium salt is added, and the other steps and conditions are the same as in Example 1. The obtained electrolyte is named SA / PVAA. The preparation of a sandwich structure zinc-air battery is the same as in Example 1.
[0072] Comparative Example 2
[0073] A method for preparing a dough-type electrolyte modified by a long carbon chain quaternary ammonium salt for a zinc-air battery is as described in Example 1, except that the long carbon chain quaternary ammonium salt is replaced by a short chain quaternary ammonium salt tetraethylammonium hydroxide, and the other steps and conditions are the same as in Example 1. The obtained electrolyte is named SQAS / SA / PVAA. The preparation of a sandwich structure zinc-air battery is the same as in Example 1.
[0074] Test Example 1
[0075] The electrolytes prepared in Example 1 and the comparative example were subjected to impedance and ionic conductivity tests. The impedance test method was as follows: the gel electrolyte was sandwiched between two steel foils, and its impedance characteristics were tested, such as Figure 2 In the left figure, LQSSS / PVA electrolyte shows lower resistance, indicating that it has better ionic conductivity and more efficient charge transfer. SQSSS / PVA and SS / PVA have higher impedance, indicating that their ionic conductivity and charge transfer performance are poor. Low impedance values usually correspond to better battery performance, which means that LQSSS / PVA electrolyte has better battery discharge performance and lower internal loss. By analyzing the resistance value obtained from the impedance spectrum, combined with the surface area of the steel foil and the thickness of the electrolyte, the ionic conductivity of the electrolyte can be calculated, such as Figure 2 On the right, LQSSS / PVA has the highest conductivity (close to 120mS / cm 2 ), according to the results of EIS and conductivity, long carbon chain quaternary ammonium salts performed better, providing lower electrochemical impedance and higher conductivity, and optimizing the performance of the electrolyte and the overall battery.
[0076] Test Example 2
[0077] The discharge performance test was performed on the batteries prepared in Example 1 and the comparative example.
[0078] The test method is as follows: Constant current discharge performance test, using 5mA / cm 2 The current density is tested, such as Figure 4 Left figure, compared with no quaternary ammonium salt and using short carbon chain quaternary ammonium salt, the battery assembled with electrolyte modified by long carbon chain quaternary ammonium salt has the highest discharge voltage and the longest time, and can maintain a stable voltage platform, indicating that the battery capacity is the largest and the electrolyte has excellent performance in ionic conductivity and stability. In the discharge performance comparison test at different rates, it is necessary to set 1mA / cm 2 , 3mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 , 5mA / cm 2 , 3mA / cm 2 , 1mA / cm 2 Different current densities, such as Figure 4In the right figure, the battery assembled with the electrolyte modified by long carbon chain quaternary ammonium salt can still maintain a high discharge voltage at high discharge current density, and the voltage curve is smooth, indicating that the electrolyte has excellent rate performance and good stability at high rate discharge.
[0079] Test Example 3
[0080] The batteries prepared in Example 1 and the comparative example were subjected to cycle performance tests.
[0081] Test method: Cyclic performance test, using 5mA / cm 2 The current density is 15 minutes for each charge and discharge cycle. The test results are as follows Figure 5 As shown in the figure, the battery assembled with the electrolyte modified by the long carbon chain quaternary ammonium salt has small voltage fluctuation and long stability time (about 100h, 200 cycles) during the long cycle. In contrast, the short carbon chain quaternary ammonium salt and the quaternary ammonium salt-free have obvious disadvantages in stability and life, which further verifies the important role of long carbon chain quaternary ammonium salt in optimizing the performance of electrolytes for zinc-air batteries.
Claims
1. An electrolyte, characterized in that The electrolyte components include an electrolyte framework, a salt modifier and an electrolyte matrix; wherein the electrolyte framework is a cross-linked network framework formed by components containing sodium alginate SA, a polymer and a long carbon chain quaternary ammonium salt.
2. The electrolyte according to claim 1, characterized in that The salt modifier and the electrolyte matrix are arranged in an electrolyte frame; the electrolyte is in a dough shape; The long carbon chain quaternary ammonium salt is a quaternary ammonium salt having an alkyl carbon chain number of 9 or more.
3. The electrolyte according to claim 2, characterized in that The long carbon chain quaternary ammonium salt includes one or more of dodecyltrimethylammonium chloride DTAC, hexadecyltrimethylammonium chloride CTAC, and octadecyltrimethylammonium chloride STAC.
4. The electrolyte according to claim 1, characterized in that The polymer includes one or more of cyclodextrin, polyacrylic acid PAA, polyethylene glycol PEG, polyvinyl alcohol PVA, sodium polyacrylate PAANa, polyacrylamide PAM, polyvinylidene fluoride PVDF copolymer, and polyethylene oxide PEO.
5. The electrolyte according to claim 1, characterized in that The salt modifier includes one or more of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, potassium iodide, potassium bromide, 2-acrylamido-2-methylpropanesulfonic acid sodium salt, sodium dodecylbenzenesulfonate, and 1-ethyl-3-methylimidazole acetate EMIMAc; The electrolyte matrix includes an alkaline electrolyte matrix or a neutral electrolyte matrix; The alkaline electrolyte matrix includes KOH; the neutral electrolyte matrix includes a salt formed by zinc trifluoromethanesulfonate and lithium bistrifluoromethanesulfonyl imide.
6. A method for preparing an electrolyte, comprising: (1) mixing a long carbon chain quaternary ammonium salt and a polymer solution, and then mixing with an initiator and a cross-linking agent, and degassing to obtain a mixed solution; (2) The mixed solution, electrolyte matrix, and salt modifier are mixed to undergo a cross-linking reaction, and then sodium alginate SA is added and mixed to obtain an electrolyte.
7. The preparation method according to claim 6, characterized in that: In the step (1), the mass ratio of the long carbon chain quaternary ammonium salt, the initiator, and the cross-linking agent is (30-100):(1-3):(1-2); The polymer solution in step (1) is a polymer aqueous solution; the mass percentage concentration of the polymer solution is 0.5-50%; the initiator in step (1) is one of potassium persulfate, ammonium persulfate, and azobisisobutyronitrile; the crosslinking agent is one of N,N'-methylenebisacrylamide, glutaraldehyde, and diglycidyl ether; In the step (1), the long carbon chain quaternary ammonium salt is a ground long carbon chain quaternary ammonium salt; The degassing in step (1) is to remove bubbles by vacuuming at room temperature.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the electrolyte matrix in step (2) to the polymer solution in step (1) is (0.5-30): (1-5); In step (2), the electrolyte matrix and the salt modifier are added to the mixed solution under ice bath conditions; The cross-linking reaction in step (2) is carried out at 40-80° C. for 15-40 minutes; After adding sodium alginate in the step (2), the mixture is stirred and mixed until the granular feeling disappears.
9. A zinc-air battery, characterized in that: The zinc-air battery comprises a positive electrode, a negative electrode and the electrolyte according to claim 1.
10. Use of the electrolyte according to claim 1 and the zinc-air battery according to claim 9 in energy storage, flexible electronics and green energy systems.